An evaluation of the impact of soil carbon enhancing practices on farm output in Western Kenya - Karanja Ng'ang'a, Stanley; Anyango Jalang'o, Dorcas; Girvetz, Evan Hartunian (African Association of Agricultural Economists, 2019)
Sustainable agricultural practices that enhance soil carbon simultaneously improve farm yields and income. Despite the expansive literature on adoption of soil carbon practices in Kenya, there is limited information on the impact of the elemental practices on farm output. This study attempts to fill this literature gap by evaluating the impact of soil carbon practices on farm output in Western Kenya. Results show that agroforestry, maize-legume intercropping, terracing and use of inorganic fertilizer are dominant soil carbon practices. Howbeit, the propensity score matching results reveal that maize-legume intercropping solely has observable impact on farm output. On average, farmers involved in the practice have an increase of 27% on maize output as opposed to those who don’t, and as such adoption could improve their welfare. The findings suggests that interventions targeted on facilitating the uptake of maize-legume intercropping among resource-poor rural smallholder farmers should be pursued.